Theoretical-methodological notes: Stephen J. Ball's contributions for education policies research - Mauricio de Sousa (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2018)
This paper presents some theoretical-methodological contributions by Stephen J. Ball for educational policy research. Throughout the text the following concepts are analyzed: politics as text and discourse, policy cycle approach, theory of enactment, new managerialism and performativity. It is concluded that such concepts developed by Ball, when analyzing the British and European scenarios, can contribute to the research of Brazilian educational policy, especially those focused on the policy in large scale external evaluation.